EFFECTIVENESS OF DIQUAT, BOTH ISOLATED AND ASSOCIATED WITH COPPER SOURCES IN CONTROLLING THE Hydrilla verticillata SUBMERGED MACROPHYTES AND ANKISTRODESMUS Gracilis microphyte - MALASPINA,I.C. (2017)
ABSTRACT The goal of this study was to evaluate the effectiveness of diquat, both isolated and associated with copper sources (oxychloride and hydroxide) in controling the H. verticillata submerged macrophyte and the A. gracilis microalgae. For this purpose, 10.0 cm H. verticillata young branches and 300 mL of A. gracilis culture were used. The experiments were performed in laboratory and the tested diquat concentrations were: 0.1; 0.2; 0.4; 0.8; 1.2; and 1.8 mg L-1, either isolated or added with 1.0% copper oxychlorideand hydroxide, as well as a control sample. On day 3, 7, 11, 21 and 30 after application, phytotoxicity signs were evaluated and on day 60 after application, green and dry biomass production and plant length were measured. To obtain dry mass, plants remained in a greenhouse with forced air circulation at 65.0 oC, until constant weight. On day 1, 7, 15, 21, 30, 45 and 60 after application, the concentration of chlorophyll a in the water was assessed. The herbicide diquat used alone or in combination with sources copper oxychloride and hydroxide was effective in the control of H. verticillata and microalgae A. gracilis.